Antecedents of Technology Adoption by Manufacturing Firms in the UAE - Saqer Saif Almehairbi, Khalfan Mohamed; Jano, Zanariah; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
Technology adoption growth has become a primary motivator for individuals, businesses, and governments in this competitive world. Hence, this paper presents a study of antecedents of technology adoption by manufacturing firms in the UAE. This study has identified 19 antecedents of technology adoption growth from the literature. A questionnaire survey was conducted by distributing 400 questionnaires to the manufacturing firms’ employees involved in production operations in UAE. However, only 330 valid questionnaires were for data analysis. The collected data was analysed to rank the antecedents based on its influenced on adopting new technology in the UAE's manufacturing sector. The ranking was based on mean score and standard deviation values of the antecedents. It was found that the five highest ranks are organization antecedent ranked first with a mean value of 4.50, followed by Time for implementation ranked second with a mean value of 4.44. Technique for operating technology ranked third with a mean value of 4.38, compatibility ranked fourth with a mean value of 4.37, relative advantage ranked fifth with a mean value of 4.36. Following, the collected data were analysed for each antecedent effectiveness in technology adoption. Out of 19 identified antecedents of technology adoption, it was found that ten of it have strong level of effect, while nine have high level of influences on the technology adoption growth. The study's findings can help government agency to formulate policy related to technology adoption growth in UAE manufacturing sector and this will improve the UAE's business and economic growth improves their performance and productivity by leveraging technology.